PERAN KEPALA DESA UNTUK MEUJUDKAN SWADAYA MASYARAKAT DILIHAT DARI PEMBANGUNAN INFRA STRUKTUR DESA STUDI PADA KASUS DI DESA CINTA DAMAI KECAMATAN SUNGAI LILIN MUSI BANYUASIN - Siti Hartina Aprilia; Novia Kencana; Doris Febriyanti (Jurnal Pemerintahan dan Politik, 2019)
The success of the construction of a village, one of which is influenced by the role of the head of the village, thus the role of the head of the village became important indispensable in the process of the construction of the village in order to make way for construction as well as increase public awareness for participating in the development of the village. This research aims to know the role of the village chief in the village of Peace to realize non-governmental Society through his role as the village head in making policies, decisions, and budgets are used for the construction. Theory research is the theory of path goal theory and transformational. The results of the research through the theory of path goal where the role of the head of the village seen from the theory of transformational development and seen in terms of his leadership or his psychological, pointed out that the role of the head of the village of Peace to realize the Ngos, has been carried out through a work program the village chief peace-loving. Work program the village chief peace-loving one, namely enhancing peace-loving Village infrastructure development, with the village development programme that is to be able to realize the swadya of the people.Keyword : Role of Village Head, Development, Self-Helping Community